Composition, Antimicrobial and Antioxidant Activity of Supercritical Fluid Extract of Elsholtzia ciliata. Issue 2 (4th March 2018) - Ma, Jun; Xu, Rui-Rui; Lu, Yao; Ren, Di-Feng; Lu, Jun
Abstract: Elsholtzia ciliate is mainly used in folk medicine for the treatment of cold, fever, dysentery and digestion disorder. The aim of our study is to investigate the composition of supercritical fluid extract of Elsholtzia ciliate and to study its antimicrobial and antioxidant activity. In our research, the extract of Elsholtzia ciliate was extracted using the CO2 supercritical fluid extraction (SFE) and then its chemical constituents were analyzed by gas chromatography-mass spectrometry (GC-MS). Seventeen components were identified by GC-MS analysis which mainly include elsholtzia ketone (9.16 %), 9, 12, 15-octadecatrienoic acidethyl ester (13.74 %), 9, 12-octadecadienoic acid (13.59 %), tetratriacontane (11.25 %), and octacosane (9.49 %). A good antibacterial effect of the extract has been proved by an experiment performed in an antibacterial assay with minimum inhibitory concentration (MIC) values and inhibition zone. Moreover, the extract showed low levels of antioxidant capacity in the DPPH assay, as well as slight inhibitory activity in a β-carotene bleaching assay. The results of this research show that the extracts of Elsholtzia ciliata might be a natural potential source of food preservatives and antioxidants.